2007
DOI: 10.1002/pam.20287
|View full text |Cite
|
Sign up to set email alerts
|

Redlining or risk? A spatial analysis of auto insurance rates in Los Angeles

Abstract: Auto insurance rates can vary dramatically, with much higher premiums in poor and minority areas than elsewhere, even after accounting for individual characteristics, driving history, and coverage. This paper uses a unique data set to examine the relative influence of place-based socioeconomic characteristics (or redlining) and place-based risk factors on the place-based component of automobile insurance premiums. We use a novel approach of combining tract-level census data and car insurance rate quotes from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Markkula (2004) also noted that insurers may be more likely to deny service to minority and low-income customers, as well as drivers who were previously uninsured. However, one study that evaluated how the size of the minority population (percentage that is black or Latino), the percentage under the poverty line, and crime rates (among other variables) affected insurance premiums, found that any significance from ethnicity indicators may be due to an interaction with poverty indicators, for they found poverty had a larger coefficient (Ong and Stoll 2007). Hence we will include the poverty rate, but not race or ethnic indicators.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Markkula (2004) also noted that insurers may be more likely to deny service to minority and low-income customers, as well as drivers who were previously uninsured. However, one study that evaluated how the size of the minority population (percentage that is black or Latino), the percentage under the poverty line, and crime rates (among other variables) affected insurance premiums, found that any significance from ethnicity indicators may be due to an interaction with poverty indicators, for they found poverty had a larger coefficient (Ong and Stoll 2007). Hence we will include the poverty rate, but not race or ethnic indicators.…”
Section: Independent Variablesmentioning
confidence: 99%
“…As an alternative, (Campbell et al, 2008) use proprietary data on unsecured debt. Other studies on redlining use house market data (Aalbers, 2007;Ezeala-Harrison et al, 2008), consumer credit card data (Brevoort, 2011;Cohen-Cole, 2009), and insurance data (Ong & Stoll, 2007;Ross & Tootell, 2004).…”
Section: Credit Marketsmentioning
confidence: 99%
“…However, one simulation study in the Los Angeles region found that covered insurance risks are indeed higher for people living in minority or low-socioeconomic status neighborhoods-but the difference in insurance premiums exceeds what is justified by the difference in risk (Ong and Stoll, 2007). A more recent study analyzed data on premium quotes and incurred insurance losses for states that kept ZIP code-level records of insurance payouts .…”
Section: Redliningmentioning
confidence: 99%